Factors Associated with Decline of Test Scores of High School Seniors, 1972 to 1980. A Study of Excellence in High School Education Educational Policies, School Quality, and Student Outcomes. Contractor Report - Rock, Donald A.; Educational Testing Service, Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
Using data from the National Longitudinal Study of the High School Seniors Class of 1972 (NLS) and from High School and Beyond (HS&B), this study documents changes in the academic achievement of high school seniors between 1972-1980. It also identifies the school and student factors related to these changes. Its purpose is to inform policymakers about the sources of current educational problems and to identify educational practices important for educational excellence. The findings indicate declines on all three achievement tests, with the largest declines in vocabulary and reading. Numerous and significant changes were identified in the characteristics of seniors, their homes and families, their schools, and their attitudes and behavior. A "step down" analysis of covariance was used to estimate how these changes separately affected the average score decline. Path analysis was employed to explore differences in the educational processes experienced by 1980 subpopulations with larger score declines and their 1972 counterparts. Results indicate that the changes from 1972 to 1980 at both the school and student level that contributed most to test score decline were: (1) a greater likelihood of being in a general or vocational curriculum rather than an academic one; (2) a drop in the frequency of taking traditional college preparation core courses; (3) a decrease in homework; and (4) increase in student dissatisfaction with the lack of academic emphasis in schools. Findings support the policy recommendations of recent national reports in regard to curriculum, course content, homework and programs for special populations. (BS)
Sponsoring Agency: Center for Statistics (ED/OERI), Washington, DC.
Contract Number: OE-300-83-0247.
Educational level discussed: High Schools.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Achievement Tests; College Preparation; Educational Assessment; Educational Change; Educational Facilities Improvement; Educational Policy; Family Characteristics; Federal Programs; High School Seniors; High Schools; Institutional Characteristics; Longitudinal Studies; National Surveys; School Demography; Secondary School Curriculum; Student Attitudes; Student Characteristics; Test Results; High School and Beyond (NCES) -- Test Score Decline; National Longitudinal Study High School Class 1972; Reports, Research; Numerical/Quantitative Data